The Impact of Covid-19 Pandemic on Mental Health and Lifestyle in the Population of Kaunas City (Baltic Journal of Sport and Health Sciences, 2022)
Background. Nationwide lockdowns, encompassing mass quarantine under stay-at-home ordinances, have already proven effective in controlling the COVID-19 outbreak. A prolonged homestay may also be associated with potential side effects, which may jeopardize people’s health. Some undesirable consequences of prolonged homestay can be physical inactivity, behavioral addiction disorders and social isolation (Henry, Bovo, & Sanchis-Gomar, 2020). The aim of the study is to analyse the impact of COVID-19 on mental health and lifestyle in the population of Kaunas city. Methods of research. anonymous online survey, which included questions on demographics, eating habits, alcohol and tobacco consumption, physical activity (Global Physical Activity Questionnaire), sleep quality (Pittsburgh sleep quality index) and mental health (Patient Health Questionnaire – 9). Results. the study involved 388 respondents from Kaunas city. Women accounted for 80,7 %, and men for 19,3 % of respondents. Average of sedentary behavior during the pandemic – 430, 93 ± 233,47 min., before the pandemic – 324, 42 ± 216,21 min. (p